Towards sustainable development of oil and gas industry in Pengerang, Malaysia: An evaluation of social economic impact assessment - Yusoff, Ismail; Md Yusof, Aminah (2013)
The research seeks to investigate the social and economic impacts of the Oil and Gas Industry in Johor,Malaysia.The industry has been established by the Government of Malaysia in 2011 involving 22,500 acres of land to be acquired by Petronas and Dialogue Group in the southern part of West Malaysia.The research would utilize the Socio-Economic Impacts Assessment methodology focusing on the case study areas.The investigation would be by way of conducting interviews with randomly chosen affected landowners and agents involved in the case study areas.Data on related socio economic impact are in the form of primary and secondary sources.The secondary data is based on published materials like structure and local plans, data from reports on rebranding and planning studies whereas primary data will be collected by interviews with agents and agencies as selected key players involved directly or indirectly with the Oil and Gas industry in the case study areas.Interviews will be conducted on various parties within 25 km radius of the areas.Analyzed data is presented graphically and, in direct and indirect quotations to achieve the predetermined objectives of the research.The results affirm the need for holistic thinking and collaborative, integrated problem solving for the effort of providing land in the market for sustainability of the oil and gas hub. In the end, the paper recommends suggestions to sustain the social and economy of the country alongside the vision of The Economic Transformation Programs( ETP) and the driving forces to achieve the National Key Result Areas (NKRA) towards achieving high income nation, improving rural infrastructure and eliminating food crises.